New Media in Public Relations: A Study of New Media in Ragunan Zoo as a Tourism Destination - Febrina, Diah; Halim, Umar (UIR Press, 2020)
Globalization has made the inhabitants of the world interconnected more closely in almost every aspect of life because of the speed of information obtained. One of the important things that need to be considered in realizing the process of globalization is the development of information technology. The development of information technology has led to the emergence of new media. The new media is being used in various industries and business including in tourism industry. Public relation practitioners working in tourism industry take benefits of new media as means of communication and promotion. Ragunan Zoo is a tourist destination located in South Jakarta, Indonesia. The development of the era led to the development of strategy in introducing this tourism destination to local and overseas tourists. The types of new media that this tourism destination exploits are websites, social media, and mobile phone applications.